Case Report: Yellow Fever Vaccine-Associated Neurotropic Disease and Associated MRI, EEG, and CSF Findings - Cohen, Michelle; Nguyen, Madeline; Nix, Chad D.; Case, Brendan; Nickerson, Joshua P.; Bernard, Jacqueline; Durrant, Julia; Safarpour, Delaram; Tucker, Tarvez; Vagnerova, Kamila; Messer, William B. (Frontiers in Neurology, 2022)
Yellow fever vaccine-associated neurotropic disease (YEL-AND) is a rare and serious complication following vaccination with the 17D live attenuated yellow fever vaccine. Cases of YEL-AND have presented as acute inflammatory demyelinating polyneuropathy, acute disseminated encephalomyelitis, and meningoencephalitis. To date, intracranial imaging of the progression and resolution of this disease has been minimally depicted in the literature. We present the case of a 67-year-old woman who developed YEL-AND following vaccination. Her diagnosis was complicated by imaging findings consistent with variant Cruetzfeldt Jakob Disease. Her clinical history and the progression of her intracranial imaging is discussed in this case report.